Electronic Structure of Hydrogenated and Surface-Modified GaAs Nanocrystals: Ab Initio Calculations - Hamsa Naji Nasir; Mudar A. Abdulsattar; Hayder M. Abduljalil (Advances in Condensed Matter Physics)
Two methods are used to simulate electronic structure of gallium arsenide nanocrystals. The cluster full geometrical optimization procedure which is suitable for small nanocrystals and large unit cell that simulates specific parts of larger nanocrystals preferably core part as in the present work. Because of symmetry consideration, large unit cells can reach sizes that are beyond the capabilities of first method. The two methods use ab initio Hartree-Fock and density functional theory, respectively. The results show that both energy gap and lattice constant decrease in their value as the nanocrystals grow in size. The inclusion of surface part in the first method makes valence band width wider than in large unit cell method that simulates the core part only. This is attributed to the broken symmetry and surface passivating atoms that split surface degenerate states and adds new levels inside and around the valence band. Bond length and tetrahedral angle result from full geometrical optimization indicate good convergence to the ideal zincblende structure at the centre of hydrogenated nanocrystal. This convergence supports large unit cell methodology. Existence of oxygen atoms at nanocrystal surface melts down density of states and reduces energy gap.